Anterior Abdominal Wall Pain - A. I. Dolgushina; M. I. Karpova; I. A. Karpov; N. B. Nadtochiy; A. A. Saenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present modern approaches to the differential diagnosis and treatment of anterior abdominal wall pain.Key points. Pain in the anterior abdominal wall is a common reason for visiting a gastroenterologist and is often misinterpreted. Signs that distinguish it from visceral and parietal pain include local character, a positive Carnett sign and the effectiveness of local anesthetic injection. Among the main causes, it is necessary to highlight diseases that are not accompanied by a palpable mass in the anterior abdominal wall (anterior cutaneous nerve entrapment syndrome, ilioinguinal nerve syndrome, slipping rib syndrome, radiculopathy and myofascial pain syndrome). Another group of causes of pain in the anterior abdominal wall is represented by diseases in which areas of infiltration (tumors, endometriosis, infections) or hernial protrusions are determined, in which radiation methods play an important role in diagnosis.Conclusion. Knowledge of pathognomonic clinical and instrumental signs is the basis for differential diagnosis and choice of treatment strategy for pathology of the anterior abdominal wall.